2017
DOI: 10.1016/j.tube.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping and rifampicin and isoniazid resistance in Mycobacterium bovis strains isolated from the lymph nodes of slaughtered cattle

Abstract: In developing nations, 10-20% of the human cases of tuberculosis are caused by Mycobacterium bovis. However, this percentage may be underestimated because most laboratories in developing countries do not routinely perform mycobacterial cultures, and only a few have the systems in place to identify M. bovis. There are few studies investigating genotypic diversity and drug resistance in M. bovis from animal and/or human infections. The genotypic diversity of M. bovis strains obtained from bovine lymph nodes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 43 publications
3
29
4
1
Order By: Relevance
“…Only one lymph node showed the simultaneous isolation of R. equi and M. bovis (data not shown). This result is not surprising as mycobacteria are recognized as a major agent of tuberculoid gross changes in cattle (Dvorska et al., ; Sahraoui et al., ), including in Brazil (Franco et al., ). Nevertheless, a high prevalence (31.0%) of R. equi recovered from lymphadenitis was found in cattle in the current study, indicating that this microorganism should be considered itself an agent of lymphadenitis in this species (Dvorska et al., ; Flynn et al., ; Soedarmanto et al., ), and an important pathogen to the differential diagnosis of mycobacteriosis, as lesions caused by those bacteria are macroscopically indistinguishable (Soedarmanto et al., ).…”
Section: Resultsmentioning
confidence: 91%
“…Only one lymph node showed the simultaneous isolation of R. equi and M. bovis (data not shown). This result is not surprising as mycobacteria are recognized as a major agent of tuberculoid gross changes in cattle (Dvorska et al., ; Sahraoui et al., ), including in Brazil (Franco et al., ). Nevertheless, a high prevalence (31.0%) of R. equi recovered from lymphadenitis was found in cattle in the current study, indicating that this microorganism should be considered itself an agent of lymphadenitis in this species (Dvorska et al., ; Flynn et al., ; Soedarmanto et al., ), and an important pathogen to the differential diagnosis of mycobacteriosis, as lesions caused by those bacteria are macroscopically indistinguishable (Soedarmanto et al., ).…”
Section: Resultsmentioning
confidence: 91%
“…Multidrug-resistant M. bovis outbreaks in humans have occurred, some with serious consequences [ 16 , 18 , 47 ]. M. bovis isolates from cattle with drug resistance towards either RIF or INH or towards both drugs have already been documented [ 23 , 29 ]. Drug susceptibility surveillance of M. bovis from animals may therefore contribute to preventing the transmission of multidrug-resistant strains to humans and to controlling possible outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…While mycobacteria isolated from human cases are generally assessed for drug susceptibility, studies on antitubercular drug susceptibility testing of M. bovis and M. caprae isolated from animals are limited [ 23 29 ]. So far, M. bovis isolates from cattle resistant to INH and rifampin (RIF) have been documented in Italy [ 23 ] and Brazil [ 29 ], to the best of our knowledge. Monitoring of antitubercular drug resistance of M. bovis isolated from animals may thus contribute to reducing the risk of drug-resistant M. bovis transmission from animals to humans and among human beings.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to consider the occurrence of MDR M.bovis because many studies provided evidence that this pathogen has been isolated from animals. A recent study published in 2017 reported that Mycobacterium bovis resistant to both rifampicin and isoniazid in a study conducted in Brazil [42].…”
Section: Figure 1: Stages For Eligibility Criteria and Study Selectiomentioning
confidence: 99%